Historical and geographical review of Gaul in work «Ashkharatsuyts» - Harutyunyan, Hakob Zh. (Journal of the Belarusian State University. History, 2023)
The text of the unique historical-geographical work «Ashkharatsuyts» («Ancient Armenian geography») is analysed. In particular, fragments of the text dedicated to Gaul, which was of great importance among the countries of old Europe, are studied. It is shown that Gaul was located mainly on the territory of modern France, but at the same time it covered some regions of other modern countries, such as Italy, Luxembourg, Belgium, the Netherlands and Switzerland. It is noted that not only ancient historians were engaged in the study of Gaul, which is confirmed by other ancient sources that mention this country. It is proved that, despite the brevity of the fragment of the text of the Armenian source dedicated to the description of Gaul, it contains valuable information about the borders, the administrative-territorial division of the country, as well as its geographical and ethnographic description. It is concluded that all these data require scrupulous hermeneutic consideration.